0
$\begingroup$

I must find a power series solution for:

$$y''-xy'-y =0$$

centered at $x_0 = 0$

I'm supposing it in the form:

$$y = \sum_{n=0}^{\infty}a_nx^n$$

so:

$$y' = \sum_{n=1}^{\infty}na_nx^{n-1}$$ $$y'' = \sum_{n=2}^{\infty}n(n-1)a_nx^{n-2}$$

I've shifted the index of all of them, so I got:

$$y = \sum_{n=0}^{\infty}a_nx^n$$ $$y' = \sum_{n=0}^{\infty}(n+1)a_{n+1}x^{n}$$ $$y'' = \sum_{n=0}^{\infty}(n+2)(n+1)a_{n+2}x^{n}$$

so,substituting it in the differential equation, I get:

$$\sum_{n=0}^{\infty}(n+2)(n+1)a_{n+2}x^{n}-x\sum_{n=0}^{\infty}(n+1)a_{n+1}x^{n}-\sum_{n=0}^{\infty}a_nx^n = 0$$

The idea now is to group them all and isolate the $x^n$ coefficient, but what should I do with that $x$ multiplying $y'$? It'll shift the index of the sum and it'll have the term $x^{n+1}$ in it, making it impossible to isolate $x^n$

$\endgroup$
5
  • 1
    $\begingroup$ So isolate $x^{n+1}$. You might need to consider the first few values $a_0, a_1,..$ separately as they are not present in all three sums. $\endgroup$ – Paul Nov 25 '16 at 11:44
  • 1
    $\begingroup$ It's probably more efficient if you multiply the $x$ inside the sum before you shift the index. $\endgroup$ – B. Goddard Nov 25 '16 at 11:45
  • $\begingroup$ @B.Goddard but I have two choices: either I start at $n=0$ and $x^{n+1}$ or I start at $n=1$ and $x^n$, I can't do both :c $\endgroup$ – Guerlando OCs Nov 25 '16 at 15:07
  • 1
    $\begingroup$ The standard way is to multiply the $x$ inside. Then shift the index, so you end up starting at $n=1$. Then take the $n=0$ terms out of the other two sums and move them to the front of the expression. Now all three sums start at $n=1$. $\endgroup$ – B. Goddard Nov 25 '16 at 15:09
  • $\begingroup$ Put the x in the middle term inside the summation and shift the index again.. $\endgroup$ – DanielWainfleet Oct 18 '17 at 20:00
1
$\begingroup$

If $y=\sum_{n\ge0}a_nx^n$, then $$ y'=\sum_{n\ge1}na_nx^{n-1} $$ and $$ y''=\sum_{n\ge2}n(n-1)a_nx^{n-2}=\sum_{n\ge0}(n+2)(n+1)a_{n+2}x^n $$ Therefore $$ y''-xy'-y=\sum_{n\ge0}(n+2)(n+1)a_{n+2}x^n-\sum_{n\ge0}na_nx^{n}-\sum_{n\ge0}a_nx^n $$ so $$ (n+2)(n+1)a_{n+2}-na_n-a_n=0 $$ or $$ (n+2)a_{n+2}-a_n=0 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.